DETECTION OF SERUMNEUTRALIZING ANTIBODIES IN CATTLE VACCINATED AGAINST FOOT-AND-MOUTH DISEASE IN FIELD - ΠΑΠΠΟΥΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 1973)
A serologic?.! investigation for serum neutralizing antibodies against Foot—and—Mouth Disease (FMD) was carried out in cattle of two villages in the Evros department (near thv. turkish border), where a vaccination is being applied twice a year since 1964,using type Ο and sometimes A22 FMD vaccines. This investigation gave the following results : On 15 calves, aged 5-7 months, vaccinated or.ee no antibodies were detected before vaccination, whereas 3 weeks later only 3 animals (20° o ) showed acceptable antibody titres, that is more than 1.2. The other calves had titres 0.3 to 1.2 (7 animals = 46.6%) and in 5 calves (33.4%) no antibodies were detected. On 80 plurivaccinated cattle, 3 weeks after the last vaccination made 8 months after the previous one, the ?ntibody titres were higher than 1.2 in 75 animals (60 animals or 73,7% with a high titre that is more than 1.8, 15 animals or 19,4% with a titre 1.2 to 1.8)and only in 5 animals (6.6%) the titres were lower than 1.2. On half of the above cattle, the following titres were found before the last vaccination : )1.8 in 17 animals (42.5%), 1.2 to 1.8 in 11 animals (27.5%) and lower to 1.2 in 12 animals (30%). 1 he bovine of the one village showed a greater percentage of animals with high antibody titre comparing to the other one. This might be due to a different antigenic capacity of the vaccines used. For determining the neutralizing antibody titre the method of constant virus units and variable serum dilutions was applied using 100 TCID50/ml. The conclusion from the above results is that the bovine population of the Evros region, except the calves who are poorly immunized, ha.d a serum neutralizing antibody level satisfactory enough 8 months after vaccination and much better 3 weeks after the last vaccination. It is believed that this antibody level is related to the strong immunity in bovine of the Evros region ag.dnst the natural infection. In fact, the Foot— and—Mouth Disease outbreaks, type O, reported the last decade in this neuralgic region were very few and the most important of very limited extention, which fact gives reason to the vaccination policy followed until today for creating a buffer zoie.